Exploiting solid lipid nanoparticles and nanostructured lipid carriers for drug delivery against cutaneous fungal infections - Araujo, Victor Hugo Sousa [UNESP] (2020)
Several types of cutaneous fungal infections can affect the population worldwide, such as dermatophytosis, cutaneous candidiasis, onychomycosis, and sporotrichosis. However, oral treatments have pronounced adverse effects, making the topical route an alternative to avoid this disadvantage. On the other hand, currently available pharmaceutical forms designed for topical application, such as gels and creams, do not demonstrate effective retention of biomolecules in the upper layers of the skin. An interesting approach to optimise biomolecules' activity in the skin is the use of nanosystems for drug delivery, especially solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), which in the past decade has shown advantages like increased adhesiveness, great occlusive properties and higher biomolecule deposition in stratum corneum when designed for topical application. Considering the demand for more effective therapeutic alternatives and the promising characteristics of SLN and NLC for topical application, the present study sought to gather studies that investigated the potential of using SLN and NLC for the treatment of cutaneous fungal infections. Studies demonstrated that these nanosystems showed optimisation, mostly, of the effectiveness of biomolecules besides other biopharmaceutical properties, in addition to offering potential occlusion and hydration of the applied region.